A method of designing high-voltage power using transformer parameters. Issue 1 (May 2021) - Zhang, Junling; Jin, Renbo
Abstract: PWM high-frequency high-voltage power has different ratio in light load and heavy load; often seriously affect the equipment's indicators and reliability. In order to find out the cause of this phenomenon and avoid it well in the design, it is necessary to understand the distribution parameters of high-frequency high-voltage transformers and the effect of high-voltage rectifier circuits on circuit gain.